Pengaruh Indeks Pembangunan Manusia (IPM) dan Pendapatan Produk Domestik Regional Bruto Terhadap Tingkat Kemiskinan Kota Medan Periode 2010-2019 - Boy Sitompul (Journal of Trends Economics and Accounting Research, 2020)
Poverty is a problem tat can affect socio-economic implications in an area. The basis that can be used in measuring poverty is the human development index and income in the region. Because of that, the purpose of this study was to determine the effect of the Human Development Index (HDI) and Gross Regional Domestic Product Income at Current Prices by Business Field on the Poverty Level of Medan City. This study uses secondary data that has been available on the official website of BPS Kota Medan. From the results. The research concluded that the Human Development Index (